A new nodule-associated bacterium, Cupriavidus consociatus sp. nov. Isolated from the root nodules of Leucaena sp. and Arachis sp. growing in a cacao field in Chiapas, Mexico - Erika-Yanet Tapia-García; Belén Chávez-Ramírez; Violeta Larios-Serrato; Ivan Arroyo-Herrera; J. Antonio Ibarra; Paulina Estrada-de los Santos (PLoS ONE, 2025)
Cupriavidus is a genus of bacteria that inhabit diverse ecological niches, including plant-associated and nodulating species. A previous survey of legume plants in the south of Mexico resulted in the isolation of several bacteria. This present study describes two Cupriavidus strains isolated from the nodules of Leucaena sp. and Arachis sp. plants growing in a cacao field in Chiapas, Mexico. Both strains (LEh25T and LEh21) shared identical 16S rRNA gene sequences and 98.4% identity with Cupriavidus oxalaticus Ox1T. However, the in silico average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) values (99.99 and 99.90% similarity, respectively) indicated that they belonged to different genomic species when compared to type strains of Cupriavidus species (ANI ~ 93.2 and dDDH ~ 50% similarity). Phylogenomic analysis indicated that the novel species would be placed in the genus Cupriavidus next to C. oxalaticus Ox1T. Neither strain could fix nitrogen in a semisolid medium, and the interactions of the type strain with Phaseolus vulgaris, and Leucaena sp. revealed the formation of nodules, although these were ineffective. The genomic analysis demonstrated the presence of nitrogen fixation and nodulation genes with the same organization as in other strains of Cupriavidus and Paraburkholderia, although lacking NodB. To complement the study of the novel species, the strains were phenotypically and chemotaxonomically analyzed, with the results indicating differences with C. oxalaticus Ox1T and other similar type strains of Cupriavidus species. From these results, we propose the novel species Cupriavidus consociatus sp. nov. with the type strain LEh25T=TSD-314T = CDBB B-2085T.